A comparative study of the trait of endurance among senior basketball players according to the variables of playing positions and the height. - bouaita, Toufik; ait lounis, Mourad; keridiche, Mohamed Lamine (sports creativity, 2025)
The aim of this study was to find out differences in endurance capacity according to playing positions and height variable among basketball players, in order to determine the most distinguished playing positions in endurance capacity. For this purpose, we have used the descriptive comparative approach on a sample of 22 players of senior category, who were randomly selected. After Statistical treatment of data, the researchers have concluded that: 1_The 1st hypothesis is not supported since there are no differences of statistical significance in endurance capacity between players according to playing positions. 2_The 2nd hypothesis is not supported too since there are no differences of statistical significance in endurance capacity between players according to height variable (Category of less than 190 cm, Category of 190 cm or more).